The Sion Treasure reconsidered - Arı, Ahmet, author.
1 online resource.
Keywords: "In 1963 a collection of 57 silver vessels was discovered during illegal excavations by villagers in Antalya Province, Turkey. The treasure is now divided between five collections: Antalya Museum (Turkey); Dumbarton Oaks (USA); a private collection in Geneva; and the Digby-Jones and Hewett collections (UK). This book builds on the studies of the Sion Treasure and examined questions regarding silver mining, manufacture, and the economic and cultural role of the silver vessels. It considers the treasure using the concept of the cultural biography of objects. The vessels from the Sion treasure have not previously been considered in this context and the book highlights the fact that the value and significance of the objects at the time they were created does not lie exclusively in their visual characteristics and aesthetics since their relationship to, and with, people is also significant. While their functionality lends them one life story, another biography is gained through their users, in terms of their producers, patrons, and the individuals within the church, not only the clergy, who engaged with the objects. The Sion Treasure Reconsidered will appeal to students and scholars alike interested in Byzantine cultural and material history and medieval material history in general"--